Wheat Mds-1 encodes a heat-shock protein and governs susceptibility towards the Hessian fly gall midge - Liu, Xuming; Khajuria, Chitvan; Li, Jiarui; Trick, Harold N.; Huang, Li; Gill, Bikram S.; Reeck, Gerald R.; Antony, Ginny; White, Frank F.; Chen, Ming-Shun (My University, 2013)
Gall midges induce formation of host nutritive cells and alter plant metabolism to utilize host resources. Here we show that the gene Mayetiola destructor susceptibility-1 (Mds-1) on wheat chromosome 3AS encodes a small heat-shock protein and is a major susceptibility gene for infestation of wheat by the gall midge M. destructor, commonly known as the Hessian fly. Transcription of Mds-1 and its homoeologs increases upon insect infestation. Ectopic expression of Mds-1 or induction by heat shock suppresses resistance of wheat mediated by the resistance gene H13 to Hessian fly. Silencing of Mds-1 by RNA interference confers immunity to all Hessian fly biotypes on normally susceptible wheat genotypes. Mds-1-silenced plants also show reduced lesion formation due to infection by the powdery mildew fungus Blumeria graminis f. sp. tritici. Modification of susceptibility genes may provide broad and durable sources of resistance to Hessian fly, B. graminis f. sp. tritici, and other pests.
Citation: Liu, X., . . . & Chen, M. (2013). Wheat Mds-1 encodes a heat-shock protein and governs susceptibility towards the Hessian fly gall midge. Nature Communication, 4(1), 2070. https://doi.org/10.1038/ncomms3070
Keywords: Gall midges; Mayetiola destructor susceptibility-1; Mds-1; Wheat; Heat-shock protein; Hessian fly